Book Reviews (Journal of Finance, 1988)
Book reviewed in this article: Business Cycles and Equilibrium . By FISCHER BLACK. New York: Basil Blackwell, 1987. Pp. xi + 180. Corporate Finance . By STEPHEN A. ROSS and RANDOLPH W. WESTERFIELD. St. Louis: Times Mirror/Mosby, 1988. Pp, xxvii + 857. Finance Theory . By ROBERT JARROW. Englewood Cliffs: Prentice‐Hall, 1988. Pp. xiv + 298.